Morphologic and textural effects of gelation and mechanochemical activation on dry or wetted simple and complex nanooxides - V. M. Gun’ko (Хімія, фізика та технологія поверхні, 2022)
The characteristics and properties of fumed oxides depend strongly on various external actions that is of importance from a practical point of view. Therefore, gelation or high-pressure cryogelation (HPC) of aqueous media pure or with 0.1 M NaCl, and mechanochemical activation (MCA) of dry or wetted powders of individual (silica, alumina, their mechanical blends) and complex (silica/titania, alumina/silica/titania, AST1, AST1/A–300) nanooxides were studied to analyze the influence of the nanooxide composition, particulate morphology, and preparation conditions on changes in the morphological and textural characteristics of treated samples. The temperature-pressure behavior of different phases (silica, alumina, and titania) under HPC can result in destroy of complex core-shell nanoparticles (100–200 nm in size) in contrast to small nonporous nanoparticles, NPNP (5–20 nm). The textural characteristics of nanooxides are sensitive to any external actions due to compaction of such supra-NPNP structures as aggregates of nanoparticles, agglomerates of aggregates, and visible structures in powders. The compaction of supra-NPNP enhances the pore volume but much weakly affects the specific surface area (with one exception of AST1) because small NPNP are relatively stable during any external actions (HPC, MCA). The compacted materials are characterized by enhanced mesoporosity shifted to macroporosity with decreasing specific surface area and increasing sizes of nanoparticles or to mesopores with increasing MCA time or amounts of water in wetted powders. At low hydration of the A–300 powder (h = 0.5 g/g), the value of SBET slightly increases if MCA is provided by stirring or ball-milling. Diminution of the freezing temperature from 208 to 77.4 K during HPC results in enhanced compaction of aggregates and agglomerates but this does not practically affect the primary nanoparticles. The degree of decomposition of core-shell nanoparticles of AST1 does not practically increase with decreasing freezing temperature from 208 to 77.4 K. Decomposition of core-shell AST1 particles is inhibited under HPC by added A–300 (1 : 1) working as a damper.